2017
DOI: 10.1371/journal.pone.0186228
|View full text |Cite
|
Sign up to set email alerts
|

Are there synergies from combining hygiene and sanitation promotion campaigns: Evidence from a large-scale cluster-randomized trial in rural Tanzania

Abstract: SummaryThe current evidence on handwashing and sanitation programs suggests limited impacts on health when at-scale interventions have been tested in isolation. However, no published experimental evidence currently exists that tests the interaction effects between sanitation and handwashing. We present the results of two large-scale, government-led handwashing and sanitation promotion campaigns in rural Tanzania, with the objective of tracing the causal chain from hygiene and sanitation promotion to changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…We found no evidence that combining water, sanitation, and hygiene interventions led to larger reductions in fecal contamination in the household environment than single interventions, a finding consistent with no additive benefit on health outcomes measured in this trial or in other studies. 15, [36][37][38][39][40] Our results indicate that the intensive WSH interventions implemented in this study did not reduce levels of fecal indicator bacteria on child hands or toys, while they slightly reduced fly presence near latrines and marginally improved visible hand cleanliness of caregivers. The lack of effect on fecal indicator bacteria measured on hands and toys has several possible explanations, including inconsistent compliance of the targeted hygiene and sanitation behaviors, failure of these specific types of WSH interventions to reduce human fecal contamination on child hands and toys, or animal fecal contamination in the household environment.…”
Section: Implications For Policy and Practicementioning
confidence: 84%
“…We found no evidence that combining water, sanitation, and hygiene interventions led to larger reductions in fecal contamination in the household environment than single interventions, a finding consistent with no additive benefit on health outcomes measured in this trial or in other studies. 15, [36][37][38][39][40] Our results indicate that the intensive WSH interventions implemented in this study did not reduce levels of fecal indicator bacteria on child hands or toys, while they slightly reduced fly presence near latrines and marginally improved visible hand cleanliness of caregivers. The lack of effect on fecal indicator bacteria measured on hands and toys has several possible explanations, including inconsistent compliance of the targeted hygiene and sanitation behaviors, failure of these specific types of WSH interventions to reduce human fecal contamination on child hands and toys, or animal fecal contamination in the household environment.…”
Section: Implications For Policy and Practicementioning
confidence: 84%
“…Prior to collecting data, a power analysis was conducted for most studies (N = 22), but this analysis was not always for an observable, behavioral measure, e.g. alternative primary outcomes included diarrhea episodes [23] and microbial counts [24]. Most of the interventions took place in schools (N = 12) or households with children (N = 13); fewer took place in pediatric settings (N = 2) or involved multiple locations, such as schools and other community centers or households (N = 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…An increase in improved sanitation use and reductions in open defecation have been demonstrated in other African countries, including Ghana, Tanzania, and Mali, where CLTS interventions led to increased latrine coverage and use. [13][14][15] In contrast to Mali, where CLTS resulted in roughly a doubling of the percentage of households with a private latrine, 14 the ZSHP resulted in a smaller relative increase in this parameter, although this change was similar to that in the studies conducted in Ghana and Tanzania. Similarly, the Mali study found a larger decrease in reported open defecation at end line (about 24 percentage points) relative to the small change in this important sanitation parameter in Zambia (four percentage points).…”
Section: Discussionmentioning
confidence: 56%
“…Like the Tanzanian and Indonesian studies, sanitation marketing, which developed the capacity of private sector players such as artisans to provide sanitation services that fulfilled the need for stronger longer lasting toilets at affordable prices, contributed to increased latrine coverage and use. 13,17 A recent meta-analysis found that CLTS was one of a handful of sanitation interventions, along with latrine subsidy/provision interventions, sewage interventions, and sanitation education interventions that had the greatest impact on latrine use and coverage. 19 There appeared to be knowledge sharing in the implementation of the project.…”
Section: Discussionmentioning
confidence: 99%